Development of Putri Water Tourism as a Tourist Attraction in Waeyoho, West Seram District, West Seram Regency - Wati, Rahma; Salakory, Melianus; Leuwol, Ferdinand Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
The definition describes the concept of tourism as an activity that can be identified as